The Influence of Abdominal Muscle Strength and Waist Flexibility on the Long Jump Results of Male Athletes - Dicky Hendrawan; Natasya Br Ginting; Ani Suryani Batubara; Andi Sinsearif Zega; Andreas Diko Gunawan Tambunan; Yunita Mandasari Yunita Mandasari; Anugrah Panca Dinata; Aszon Fisi Lahagu; Novita Putri Yani Ndruru Novita Putri Yani Ndruru; Trifosa Angelina Sembiring; Muhammad Ridho Maulana (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2024)
Objectives: To examine the relationship between abdominal muscle strength and waist flexibility with long jump performance among male collegiate athletes, and to determine the relative contribution of these factors to jump distance. Methods: A cross-sectional study was conducted with 60 male physical education students aged 18-22 years from Sekolah Tinggi Olahraga dan Kesehatan Bina Guna Medan, Indonesia. Participants underwent assessments of abdominal muscle strength (one-minute sit-up test), waist flexibility (sit-and-reach test), and long jump performance. Pearson correlation and multiple linear regression analyses were used to analyze the relationships between variables. Results: Abdominal muscle strength showed a moderate positive correlation with long jump distance (r = 0.68, p < 0.001), while waist flexibility demonstrated a moderate positive correlation (r = 0.54, p < 0.001). Multiple regression analysis revealed that abdominal strength (β = 0.52) was a stronger predictor of long jump performance than waist flexibility (β = 0.31). Together, these factors explained 57.3% of the variance in jump distance. Conclusion: Core stability and trunk flexibility are important determinants of long jump performance beyond traditional factors like lower limb power. The study recommends incorporating comprehensive core strengthening and flexibility training into long jump preparation, with a particular emphasis on abdominal muscle development.